Stability of antioxidant vitamins in commercial vitamin supplements - Lucile Tiemi Abe-Matsumoto; Geni Rodrigues Sampaio; Deborah Helena Markowicz Bastos (Universidade de São Paulo, 2019)
The stability of vitamins A, E, and C was determined in 12 brands of vitamin supplements over a 12-month storage period. The variations in concentrations of these vitamins across three different batches of five brands were measured. Vitamins A and E was determined by HPLC method, and vitamin C was measured by using potentiometric titration. All samples for stability studies were maintained at room temperature and protected from light. Measurements were carried out in the first semester of the expiration date and then every six months up to 12 months of storage. After this period, only one sample showed no significant decrease in vitamin A and E concentrations in relation to the concentrations measured at the beginning of the study. The concentration of vitamin C showed no significant decrease in 50% of the samples after 6 months of storage, although after 12 months, 92% had significant losses in concentration. The analysis of the different batches showed significant variations in the vitamin levels, which do not seem to be significant for inspection purposes considering the tolerance outlined in the legislation. Over-fortification of vitamin supplements during manufacture seems to be required, but the additional amount of supplementation will depend on each sample.